Analisis Pengaruh CAR, FDR, Inflasi, dan Suku Bunga BI terhadap ROA pada Bank Umum Syariah di Indonesia - Shafira, Ranti Firdha; Purbayati, Radia; Hadiani, Fatmi; Syarief, M. Edman (Journal of Applied Islamic Economics and Finance, 2023)
This research has the main objective of testing how influence CAR, FDR, inflation, and BI rates on ROA of Islamic in Islamic commercial banks for the 2017-2021 period.Method the method applied is a descriptive quantitative using software Eviews12. Secondary data from website Islamic commercial banks and Bank Indonesia.By using the purposive sampling methode, the subject who met the criteria were 10 banks at OJK. The chosen model is Random Effect Model (REM). This research contributes to help expand the theory of Islamic Banking that use ROA to measure financial performance.